Fifth Plan Andhra Pradesh Approach General Part 1 - Planning Commission (Planning Commission, 1972)
The Fifth Five-Year Plan (Approach: General Part I) for Andhra Pradesh presents a development strategy centered on meeting basic social needs, generating employment, and reducing regional and social disparities. Emphasizing education, public health, rural infrastructure, and housing, the Plan adopts districts as the primary units of implementation to ensure inclusive and balanced growth. In response to economic stagnation and declining central assistance, it calls for enhanced resource mobilization, strengthened cooperative institutions, and targeted investment in agriculture and backward regions. The Plan underscores coordinated state–central cooperation as essential for achieving sustainable development, equity, and economic revival.
Planning and Co-Operation Department Government of Andhra Pradesh
Planning and Co-Operation Department Government of Andhra Pradesh
Keywords: Fifth Five-Year Plan; Andhra Pradesh; Minimum Needs Programme; Employment Generation; Rural Infrastructure; Social Development; Regional Imbalances; District Planning; Resource Mobilization; Cooperative Development; Agricultural Strategy; Economic Equity